Enteral Nutrition in Preterm Infants (2022): A Position Paper From the ESPGHAN Committee on Nutrition and Invited Experts. Issue 2 (28th October 2022) - Embleton, Nicholas David; Jennifer Moltu, Sissel; Lapillonne, Alexandre; van den Akker, Chris H.P.; Carnielli, Virgilio; Fusch, Christoph; Gerasimidis, Konstantinos; van Goudoever, Johannes B.; Haiden, Nadja; Iacobelli, Silvia; Johnson, Mark J.; Meyer, Sascha; et al.
Abstract : Objectives: To review the current literature and develop consensus conclusions and recommendations on nutrient intakes and nutritional practice in preterm infants with birthweight <1800 g. Methods: The European Society of Pediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) Committee of Nutrition (CoN) led a process that included CoN members and invited experts. Invited experts with specific expertise were chosen to represent as broad a geographical spread as possible. A list of topics was developed, and individual leads were assigned to topics along with other members, who reviewed the current literature. A single face-to-face meeting was held in February 2020. Provisional conclusions and recommendations were developed between 2020 and 2021, and these were voted on electronically by all members of the working group between 2021 and 2022. Where >90% consensus was not achieved, online discussion meetings were held, along with further voting until agreement was reached. Results: In general, there is a lack of strong evidence for most nutrients and topics. The summary paper is supported by additional supplementary digital content that provide a fuller explanation of the literature and relevant physiology: introduction and overview; human milk reference data; intakes of water, protein, energy, lipid, carbohydrate, electrolytes, minerals, trace elements, water soluble vitamins, and fat soluble vitamins; feeding mode including mineral enteral feeding, feed advancement, management of gastric residuals, gastric tube placement and bolus or continuous feeding; growth; breastmilk buccal colostrum, donor human milk, and risks of cytomegalovirus infection; hydrolyzed protein and osmolality; supplemental bionutrients; and use of breastmilk fortifier. Conclusions: We provide updated ESPGHAN CoN consensus-based conclusions and recommendations on nutrient intakes and nutritional management for preterm infants